2020
DOI: 10.2147/ott.s222734
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA SOCS2-AS Promotes Leukemogenesis in FLT3-ITD+ Acute Myeloid Leukemia Through miRNA-221</p>

Abstract: Background: LncRNAs play an important role in tumorigenesis and development in tumors, but the function of lncRNA SOCS2-AS in acute myeloid leukemia (AML) is unknown. Materials and Methods: In the present study, we used RT-PCR to detect the expression of SOCS2-AS in FLT3-ITD+, FLT3-ITD-AML patients and different AML cell lines. The colony formation and CCK-8 assay were performed to analyze the proliferation ability, and the flow cytometry was performed to analyze the capacity of apoptosis in Molm-13 and MV4-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(23 reference statements)
0
5
1
Order By: Relevance
“…It has recently been reported that SOCS2-AS1 modulates FLT3-ITD activity via sponging miRNA-221 activity to maintain STAT5 signal transduction. 23 However, we observed no significant differences in FLT3 mutational status between the number of patients with (11/32 cases, 34%) and those that lacked an RDD (33/119, 28%). Moreover, the AEI also did not alter between patients that carried or lacked the FLT3-ITD mutation ( Figure 5 C).…”
Section: Resultscontrasting
confidence: 58%
“…It has recently been reported that SOCS2-AS1 modulates FLT3-ITD activity via sponging miRNA-221 activity to maintain STAT5 signal transduction. 23 However, we observed no significant differences in FLT3 mutational status between the number of patients with (11/32 cases, 34%) and those that lacked an RDD (33/119, 28%). Moreover, the AEI also did not alter between patients that carried or lacked the FLT3-ITD mutation ( Figure 5 C).…”
Section: Resultscontrasting
confidence: 58%
“…It is worth discussing the regulatory axis of lncRNA/E2F1 in this contradictory network. Supporting evidence has shown that several lncRNAs are related to FLT3‐ITD, including LncH19, 37 LncSOCS2‐AS, 38 LncTUG1 39 and LncCCAT2 40 . Among them, LncH19, LncTUG1 and LncCCAT2 were implicated in autophagy and E2F1.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al mechanically demonstrated that SOCS2-AS acts as a proto-oncogene and promotes FLT3-ITD+ AML progression by regulation of STAT5 pathway through miR-221 sponging. 107 Deng et al analyzed two datasets of miR profiling in AML patients, discovering that miR-221 was upregulated in both models. To further understand the biological function of miR-221 in AML leukemogenesis, they evaluated, both in silico and in vitro, the potential role of miR-221 in epigenetic pathway regulation, and demonstrated the existence of NCL/miR-221/NF-kB/DNMT1 epigenetic regulatory network that modulates p27kip1 and p15INK4B.…”
Section: Evolving Approaches For Mir-221 Targeting In the Novel Scena...mentioning
confidence: 99%